Exploring the interplay of psychoacoustic parameters and microphone selection in soundscape recording: a comprehensive review and practical guide - Satya, Royys Bagja Rizky; Sukmayadi, Yudi; Narawati, Tati (Gelar : Jurnal Seni Budaya, 2024)
This research explores the intricate relationship between psychoacoustic parameters and microphone selection for soundscape recording, drawing inspiration from foundational concepts introduced by Schafer and Cage. Motivated by the need to comprehend the influence of psychoacoustic dimensions—specifically frequency, sound intensity, and time—on the choice of microphones for capturing auditory environments, the study adopts Liu and Kang's systematic literature review method. This approach entails a comprehensive analysis of diverse sources to identify knowledge gaps and establish a robust theoretical foundation. The primary aim is to offer practical guidance to professionals and researchers in the field of soundscape recording. Findings underscore the efficacy of a cardioid condenser stereo microphone that aligns with the analyzed psychoacoustic parameters. This study not only contributes to advancing practices in soundscape recording but also deepens our understanding of the intricate dynamics between soundscape, psychoacoustics, and sound recording devices. By recognizing the significance of Liu and Kang's methodology, the research serves as a foundation for future experimental designs and field testing. Acknowledging Liu and Kang's contributions, the study highlights the pivotal role of their systematic literature review method in shaping the research landscape, underscoring the importance of methodological rigor in advancing our understanding of complex auditory phenomena. This research provides a comprehensive overview of the nuanced relationship between psychoacoustic parameters and microphone selection for soundscape recording, contributing to the broader discourse in the field of auditory research. The implications of this research extend to the field of sound environment recording and psychoacoustics, providing a deeper understanding, improving recording quality, developing practical guidelines, encouraging recording technology innovation, and contributing to the field of psychoacoustics.